Impacts of land use changes and land cover alteration on soil erosion rates and vulnerability of tropical mountain ranges in Borneo - Vijith, H.; Hurmain, A.; Dodge-Wan, Dominique (2018)
© 2018 Elsevier B.V. The evaluation of the impact of changes in land use on soil erosion rates and vulnerability was carried out in a tropical rainforest region of Sarawak, Borneo. Although tropical rainforest covers over 88% of the study area, supervised classification of Landsat 8 Optical Land Imager (OLI) images identified eight other classes of land cover (LC) (mixed agriculture, hill paddy, wet paddy, bushes/shrubs/grasses, exposed barren land, artificial surface, pebbles / cobbles and waterbody) with an overall classification accuracy above 80%. Maximum rate of soil loss estimated from the study area through Revised Universal Soil Loss Equation (RUSLE) was 1312 t ha-1y-1and the result aided the identification of regions with critical soil erosion vulnerability. Mean soil erosion rate in the study area was assessed to be 27 t ha-1y-1. The zones with higher soil erosion rates exceed 25 t ha-1y-1and amounted to a total area of 11%. Critical erosion zones (> 50 t ha-1y-1) were found to cover 8% and show linear characteristics which is innate of logging roads and skid trails. At the same time, over 64% of the study area showed low erosion risk with soil losses lower than 5 t ha-1y-1. Assessment made through geospatial overlay indicates dominance of four LC classes in contributing to soil erosion vulnerability and erosion rates. These are exposed barren land, secondary forest, bushes/shrubs and mixed agriculture. Field assessments confirmed the critical role of logging and hill paddy cultivation, which alter the natural terrain conditions and remove the forest cover. Although forest clearing for hill paddy cultivation removes vegetation and hence decreases protection against erosive rainfall, the sediment delivery will be relatively low due to less terrain alteration. Logging and associated activities induce the formation of soil erosion hotspots, which remain as such for several years. Logging activities generate exposed barren land which although only covers over 4% of the study area contributes more than 28% of the total soil loss.